Mapping The Contested Digital Space: A Bibliometric Analysis Of Religious Moderation And Extremism Counter-Narratives In Indonesian Millennial Studies - Rodliatul Millah; M.Muizzudin; Imam Nur Aziz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study provides a comprehensive bibliometric mapping of the contested digital landscape surrounding religious moderation and extremism counter-narratives, specifically focusing on Indonesian millennial studies. As digital platforms become the primary battlefield for ideological influencehis research evaluates how scholarly discourse has evolved to address the radicalization of the youth. Using a bibliometric approach, this study analyzed a significant corpus of high-quality documents indexed in the Scopus database from 2020 to 2025. Data visualization and thematic mapping were conducted to identify dominant subject areas, keyword co-occurrences, and the most influential research contributors. The results reveal a significant multidisciplinary shift; while traditionally a sociological concern, the field is now dominated by Computer Science (18.2%) and Engineering (16.4%), followed by Social Sciences (10.2%). This indicates that counter-extremism efforts are increasingly relying on algorithmic strategies and digital interventions. The thematic analysis highlights a "Digital-Wasathiyah" paradigm, where the integration of AI and data analytics is seen as vital for scaling moderate narratives. However, "blind spots" remain, particularly concerning the influence of Generative AI on religious authority and traditional learning models millennials. The study is limited to Scopus-indexed data. The findings imply that religious moderation in Indonesia is no longer just a theological challenge but a technological one, requiring a "human-centric" AI approach to preserve social cohesion.